Female Power in Textual Discourse and Practical Action, the Roles of Iyanifa in the Ifa Divinatory System Among the Yoruba - Adeyinka W. Olarinmoye (MultiTech Publisher, 2025)
This is a study of female power within the divinatory literature and ritual action of Ifa among the Yoruba people. The essay investigates the dialectics of the feminine between the reified textual domain of Ifa literature and the practical experiences of women in selected Ifa communities in the Yoruba towns of Ibadan, Akure, Oshogbo, Oyo, Badagry, Abeokuta, Epe and Ife. Through a focus on the agency of female diviners, Iyanifa, as dramatized in Ifa literature and as demonstrated in the actual practice of Ifa in the communities in question, this essay explores a segment of the manner in which Yorubaland navigates issues of female empowerment within the gender dynamics that shape Yoruba culture. The study used a participant observation method that spanned a decade, which allowed the researcher in observing and joining the activities of the Iyanifa and women Ifa adherents during worships and rituals. Practice and Discourse as propounded by Lila Abu-Lughod was used in drawing the differences and similarities in theory and practice of Ifa. The findings are significant to the ongoing discourses in gender constructions and reconstructions, identity issues, Yoruba spiritualties and decolonization. It is also important for Diaspora Ifa communities because it provides frameworks valuable for mapping the manner in which these communities address gender issues as they draw upon a template of religious textualisation and practical action emanating from a culture different from the Diaspora contexts in which these adaptations are taking place